0699 Predictors of Mortality in Obesity Hypoventilation Syndrome: A National Inpatient Sample Study. (25th May 2022) - Shah, Syed; Alqalyoobi, Shehabaldin; Qureshi, Waqas; Obi, Ogugua; Ibrahim, Mohammed; Teodorescu, Mihaela
Abstract: Introduction: Obesity Hypoventilation Syndrome (OHS) has been linked to adverse cardiovascular outcomes and mortality in multiple observational studies. Few single-center observational studies have reported poor outcomes of inpatient admissions in OHS. Data regarding nationwide outcomes of hospital admissions in OHS is scarce. We conducted a retrospective study to identify predictors associated with mortality using the National Inpatient Sample (NIS) database. Methods: We reviewed the NIS database to assess the outcomes of all weighted hospitalizations with an ICD 9 or ICD 10 code for OHS from 2007 to 2018. Patients with age <18, BMI <35, and ICD 9 and ICD 10 codes for neuromuscular disorders, chest wall disorders, or miscellaneous disorders of hypoventilation during the index hospitalization were excluded. The primary outcome was in-hospital mortality. We applied multivariable Cox regression modeling for the association of inpatient mortality with the diagnosis of OHS adjusted for age, sex, race, smoking history, BMI, GERD, OSA, renal failure, use of non-invasive and invasive MV, bronchoscopy, urban vs. rural hospital location, academic hospital status, COPD, asthma, acute PE, pulmonary hypertension, pneumonia and dependence on long-term oxygen or invasive or non-invasive mechanical ventilation. Hazard ratios (HR) with 95% confidence intervals (CI) were reported. Results: A total of 1, 115, 927 hospitalizations were included in the final analysis. Increasing age, Native American race (compared to White), higher BMI, renal failure, a requirement of invasive and non-invasive mechanical ventilation, acute pulmonary embolism, ILD, and pulmonary hypertension were independently associated with increased risk of mortality during the hospitalization (p-value <0.05). Female sex, academic and urban hospital status, smoking, COPD, asthma, GERD, and OSA were independently associated with reduced risk for inpatient mortality (p-value <0.05). Black, Hispanic, Asian or Pacific Islander races (compared to White) were also associated with decreased risk of mortality (p-value <0.05). Home ventilator dependence, pneumonia, or oxygen dependence were not significantly associated with the risk of death. Conclusion: Invasive mechanical ventilation (aHR 3.71, 95%CI 3.62-3.81) acute renal failure (aHR 1.93, 95%CI 1.87-2.00), and BMI > 70 (aHR 1.54, 95%CI 1.46-1.63) were the strongest predictors of inpatient mortality in our review of nationwide hospitalizations in OHS. Support (If Any):